Fiber optic test equipment and testing fiber optic links - testing fiber optic links - Johnson, Larry (IEEE, 2009)
This course provides an introductory, tutorial-type overview of key optoelectronic devices for optical communication systems, specifically, semiconductor lasers, photodetectors, optical modulators, and some WDM components. The course covers a broad range of devices with an emphasis on fundamental device physics and operating principles. Important performance parameters including design trade-offs will also be discussed. The laser section will discuss applications and the types of lasers that are utilized for specific systems. Topics include multiple quantum well lasers, distributed feedback lasers, wavelength tunable lasers and vertical cavity surface emitting lasers. Photodetector topics will cover wide-bandwidth PINs and avalanche photodiodes as well as receivers with optical preamplification. State-of-the-art integrated receiver circuits will also be discussed. In the modulator section Mach-Zehnder interferometers, and quantum-confined-Stark-effect devices will be covered. There will be a brief description of recent developments in optical switching using MEMs technology
Description based on online resource; title from title screen (IEEE Xplore Digital Library, viewed November 12, 2020)
Keywords: Optical fibers; Fiber optic cables; Film